Part 2: Agriculture growth, jobs, food security and climate: Taking action in response to IPCC - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
What does the IPCC's Fifth Assessment Report spell for food and farming and what actions can be taken? The event Agriculture growth, jobs, food security and climate: Taking action in response to IPCC which was jointly organized by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), the UK Department of International Development (DFID), the International Fund for Agricultural Development (IFAD), The Prince's Charities International Sustainability Unit, Willis, and the World Bank.The CGIAR Research Program on Climate Change, Agriculture and Food Security (https://ccafs.cgiar.org) on 3 April 2014. In the second part of the conference a panel discussion on 'What are the game changers in securing food security under climate change?' was taking place. Participating in the panel were: - Rowan M. Douglas, Chairman of the Willis Research Network, Willis - Ruth Davis, Political Director, Greenpeace UK - Gerry Boyle, Head of Advocacy, CARE International - Mike Warmington, Microfinance Partnerships Manager, One Acre Fund - Christof Walter, Independent Consultant The moderator was journalist and broadcaster Anya Sitaram. The wrap-up was given by Camilla Toulmin, Director, International Institute for Environment and Development (IIED) Closing remarks were given by Lynne Featherstone, Parliamentary Undersecretary of State for International Development (DFID).